Cancer-associated adipocyte-derived G-CSF promotes breast cancer malignancy via Stat3 signaling. (2nd April 2020) - Liu, Li; Wu, Yudong; Zhang, Cheng; Zhou, Chong; Li, Yining; Zeng, Yi; Zhang, Chunbo; Li, Rong; Luo, Daya; Wang, Lieliang; Zhang, Long; Tu, Shuo; et al.
Abstract: Adipocyte is the most predominant cell type in the tumor microenvironment of breast cancer and plays a pivotal role in cancer progression, yet the underlying mechanisms and functional mediators remain elusive. We isolated primary preadipocytes from mammary fat pads of human breast cancer patients and generated mature adipocytes and cancer-associated adipocytes (CAAs) in vitro . The CAAs exhibited significantly different gene expression profiles as assessed by transcriptome sequencing. One of the highly expressed genes in CAAs is granulocyte colony-stimulating factor (G-CSF). Treatment with recombinant human G-CSF protein or stable expression of human G-CSF in triple-negative breast cancer (TNBC) cell lines enhanced epithelial–mesenchymal transition, migration, and invasion of cancer cells, by activating Stat3. Accordantly, targeting G-CSF/Stat3 signaling with G-CSF-neutralizing antibody, a chemical inhibitor, or siRNAs for Stat3 could all abrogate CAA- or G-CSF-induced migration and invasion of breast cancer cells. The pro-invasive genes MMP2 and MMP9 were identified as target genes of G-CSF in TNBC cells. Furthermore, in human breast cancer tissues, elevated G-CSF expression in adipocytes is well correlated with activated Stat3 signal in cancer cells. Together, our results suggest a novel strategy to intervene with invasive breast cancers by targeting CAA-derived G-CSF.